ANALYSIS INCOME THE FISHERMAN BUSINESS WITH DRIFT GILLNET AT MUARA NATAL PORT AREA PASAR II NATAL VILLAGE MANDAILING NATAL DISTRICT OF NORTH SUMATRA PROVINCE - Situmorang, Ridwan Syahputra; Hamid, Hamdi; ', Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted to determine how much revenue drift fishing with gill nets in a year (travel). This research was conducted on four until ten January 2016 Pasar II Natal village Mandailing Natal district of North Sumatra province. The method used survey method of respondents 12 fisherman owner.The total investment of the owner of the fishing effort of Rp. 295,922,583.00, the average gross income of fishing effort is Rp. 402,049,500.00, the average net income of the arrest of fishing effort each year is Rp. 313,837,083.00. To get the results of the feasibility analysis on a profit of Rp. 313,837,083.00 per year (about 72), so that the profit per trip from catching 4.358.848, this advantage will be longer with the workers, so the owner can profit 2,179,424 per trip and BCR 4.56, FRR 106.05 %, 0.91 PPC period. Obstacles Drift gillnet to develop a fishing business in Pasar II Natal Village is influenced by various factors such as the length of the gear, operating costs, the number of working days, the weather and the season.Keywords: Income, Fishermen, Drift gillnet, Feasibility